Multiplex NanoSPR Molecular Biosensor for Blood Cytokine Monitoring - Agha Zeeshan Mirza (Tabriz University of Medical Sciences, 2022)
Cytokines, as protein biomarkers, have essential functions in the diagnosis, identification, andhealing of a broad range of syndromes. For the specific and accurate monitoring of immuneconditions, which change rapidly throughout the duration of disease, sophisticated sensors fordetecting cytokines are essential and will assist in clinical testing and studies of various diseases.The present manuscript briefly discusses fundamental principles applied to the development oftools for cytokine detection and new biomarker development. The latest developments in thetechnologies for highly sensitive and multiplexed cytokine quantification, with current detectioncapabilities across a broad, vibrant array, are also discussed. Finally, nanomaterial-basedcytokine sensors, currently considered new approaches, are presented from the perspective ofoptimizing the sensitivity and multiplexity of cytokine detection.